Obsessed - Patterson, James, 1947-; Born, James O. (Little, Brown and Company, 2023)
Aboard a police boat on the Hudson River, Detective Michael Bennett casts a wary eye into the cold, rough water. NYPD is searching for a murder victim-a young college student. They find her tossed in the dark waves, dressed for a night out in a sparkly black gown. The gruesome sight fills Bennett with the dread only a father could fathom. As the obsessive killer extends his spree, a pattern emerges. One that Bennett's eldest daughter fits to a disturbing degree. Now NYPD's top detective must lure the murderer into the light of day before the next deadly strike lands closer to home than Bennett could ever bear-as a parent, or as a protector.
When a killer becomes obsessed with his oldest daughter, Detective Michael Bennett will do anything to keep his family safe as he races against time to crack this superstitious killer's code.
Keywords: Bennett, Michael (Fictitious character) -- Fiction; Detectives -- Fiction; Police -- Fiction; New York (N.Y.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction